2017
DOI: 10.1002/cptc.201700108
|View full text |Cite
|
Sign up to set email alerts
|

An Acid‐Responsive Single Trichromatic Luminescent Dye That Provides Pure White‐Light Emission

Abstract: A novel acid‐responsive single trichromatic luminescent dye capable of emitting pure white light (WL) is reported. A newly designed p‐phenylene‐bridged bipyrrole bearing N‐alkylimino groups (1 a) specifically provides WL emission upon mixing with trifluoroacetic acid (TFA) in a CH2Cl2 solution. The emission originates from the trichromatic luminescent behavior of 1 a upon protonation of the imino groups. The blue‐light‐emitting 1 a exhibits dramatic color changes in fluorescence to orange and green upon mono‐ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…We previously reported the synthesis of a π-conjugated phenylene-bridged bipyrrole bearing N-alkylimino groups (BPI-1), and found that it is an acid-responsive single trichromatic luminescent dye capable of emitting pure white light (WL) (Imamura et al, 2017). The blue-light-emitting BPI-1 exhibits dramatic color changes in fluorescence to orange and green upon mono-and diprotonation, respectively, providing a wide emission band in the range of λ = 400-800 nm that provide WL when the compound is in a dynamic equilibrium between the three states.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported the synthesis of a π-conjugated phenylene-bridged bipyrrole bearing N-alkylimino groups (BPI-1), and found that it is an acid-responsive single trichromatic luminescent dye capable of emitting pure white light (WL) (Imamura et al, 2017). The blue-light-emitting BPI-1 exhibits dramatic color changes in fluorescence to orange and green upon mono-and diprotonation, respectively, providing a wide emission band in the range of λ = 400-800 nm that provide WL when the compound is in a dynamic equilibrium between the three states.…”
Section: Introductionmentioning
confidence: 99%
“…Luminescent materials exhibiting multicolor emission have attracted considerable attention due to their potential applications in many areas. Mixing emission colors in the visible region may generate white light that could be used in energy-efficient organic light-emitting diodes (OLEDs). Two or more emission bands from a single fluorophore could be exploited in the self-calibrating ratiometric sensing technologies, which offer the advantage of minimizing systematic errors originating from concentration variation, excitation power fluctuation, and photobleaching of the fluorophore . Properties of the microenvironment surrounding a multiple-emission fluorophore can be extracted through monitoring the changes of various emission bands that have uneven responses to environmental factors such as polarity , or viscosity. , …”
Section: Introductionmentioning
confidence: 99%
“…Indole with its larger aromatic structure also allowed formylation at the 3-position in 86% yield, but benzofuran provided the 2-formyl product in relatively low yield ( 1g and 1h , respectively). Since VR 2 efficiently reacted with 1 H -pyrrole, we next carried out one-pot formylation reactions of bispyrroles, which are utilized for fabricating functional supramolecular architectures and macrocyclic rings . Bispyrrole derivatives, including an aliphatic and an aromatic bridge, both provided the corresponding bisformyl products in high yields ( 1i and 1j ).…”
Section: Resultsmentioning
confidence: 99%